2017
DOI: 10.1002/job.2210
|View full text |Cite
|
Sign up to set email alerts
|

Stayers versus movers: Social capital and early career imprinting among young professionals

Abstract: We investigate what interfirm career mobility patterns would emerge if individuals are motivated by the job rewards they obtain as a function of their experience in organizations. We articulate two career strategies that individuals employ to navigate their early careers-commitment to a single employer and "job hopping" between different employers. Each strategy generates social capital (an individual's structure of social relations) but of a different kind. Embeddedness in the same organization over time deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 75 publications
2
23
0
Order By: Relevance
“…The first contribution concerns the link between employees’ career aspirations and their contribution to organizations. While recent studies have demonstrated how employees’ career mobility benefits organizations ( Dobrev and Merluzzi, 2018 ) and how organizational career management, as well as individual career investments, are beneficial for firm performance ( Crook et al, 2011 ; De Vos and Cambré, 2017 ), we extend support for this reasoning by demonstrating that employees’ career aspirations also strengthen organizational capabilities and connections. To date, research has examined career aspirations of high school and university students to understand and influence their future career paths (e.g., Schoon and Polek, 2011 ; Kitchen et al, 2017 ).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The first contribution concerns the link between employees’ career aspirations and their contribution to organizations. While recent studies have demonstrated how employees’ career mobility benefits organizations ( Dobrev and Merluzzi, 2018 ) and how organizational career management, as well as individual career investments, are beneficial for firm performance ( Crook et al, 2011 ; De Vos and Cambré, 2017 ), we extend support for this reasoning by demonstrating that employees’ career aspirations also strengthen organizational capabilities and connections. To date, research has examined career aspirations of high school and university students to understand and influence their future career paths (e.g., Schoon and Polek, 2011 ; Kitchen et al, 2017 ).…”
Section: Discussionsupporting
confidence: 56%
“…Thus, while managers are exerting much effort in identifying strategies to manage demanding business environments, employees have become more driven by their own career needs than by organizational goals. Therefore, it is not surprising that scholars have become increasingly interested in examining how organizational goals can be accomplished through employees’ career attitudes and behaviors (e.g., Fleisher et al, 2014 ; Dobrev and Merluzzi, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a growing number of studies have drawn on the idea of imprinting to describe how early experiences in a career can have a lasting effect on individual's behaviors and attitudes (e.g., Higgins, ; Dobrev & Merluzzi, ; for a review, see Marquis & Tilcsik, ). However, there has been little research on the imprinting effects of network ties; and research on the performance implications of network imprints in particular is limited to a handful of studies (e.g., McEvily et al, ; Tilcsik, ).…”
Section: Discussionmentioning
confidence: 99%
“…For employees, pursuing career goals in a specific organization has career advantages. A long-term relationship to a specific organization is a strong driver of career advancement (Bidwell & Mollick, 2015;Koch, Forgues, & Monties, 2017;Ng & Feldman, 2010a) while moving across organizations may sometimes harm individuals' careers (Baruch & Vardi, 2016;Dobrev & Merluzzi, 2018;Fuller, 2008). For organizations, committed employees are critical for attaining organizational goals and, in the longer term, ensuring continuity and growth (Cooper-Hakim & Viswesvaran, 2005;Hoekstra, 2011).…”
mentioning
confidence: 99%